(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
The purpose of the present study is to investigate the role of different emotional biases on the investment decision making of the individuals. The emotional biases studied include regret aversion bias, herd bias, overconfidence bias, locus of control and disposition effect bias. The research design adopted for the study is descriptive and exploratory in nature. The target population of the study are the individuals who had made any sort of investment from all age groups, gender and profession The sample for the study was chosen through convenience sampling and data was collected using structured and adapted questionnaire from both online and offline modes. The collected data was being analysed using structural equation modelling with the help of SPSS and Amos software. The results showed a significant effect of emotional biases on the investment decision making process of the individuals. The results of the study can be used by the investment experts, agents and professionals in understanding the emotional biases of their clients impacting their investment decisions. Thus, they can provide requisite guidance to the investors for making a rational decision. The major limitation of the study includes that the sample collected for the study is from the region of Delhi only. Also, a limited number of emotional biases are considered for the study. Future studies can be performed with other emotional biases.